2005
DOI: 10.1504/ijvics.2005.007586
|View full text |Cite
|
Sign up to set email alerts
|

The effect of variable message and speed limit signs on mean speeds and speed deviations

Abstract: Variable message signs (VMSs), showing variable speed limits, were installed on Interstate 90 (I-90) in the vicinity of Snoqualmie Pass, Washington State to reduce crash potential with effective speed and traffic flow management. This is a rural freeway location, subject to adverse weather conditions, that experiences over 75 reported vehicle crashes annually.Averages of hourly mean speed and speed deviation (standard deviation of hourly mean speed), classified by VMS on/off status, show there is a significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…Ulfarsson et al (2005) evaluated the impact of variable speed limits posted on I-90 in the vicinity of Snoqualmie Pass, Washington State using empirical data. The study concluded that the use of variable speed limits caused a statistically significant reduction in mean vehicle speeds but no Hellinga and Mandelzys 6 consistent impact on variation on speed was found.…”
Section: Driver Reaction To Speed Limitsmentioning
confidence: 99%
“…Ulfarsson et al (2005) evaluated the impact of variable speed limits posted on I-90 in the vicinity of Snoqualmie Pass, Washington State using empirical data. The study concluded that the use of variable speed limits caused a statistically significant reduction in mean vehicle speeds but no Hellinga and Mandelzys 6 consistent impact on variation on speed was found.…”
Section: Driver Reaction To Speed Limitsmentioning
confidence: 99%
“…As reported in the literature , a proper VSL control can help smooth speed transition and consequently reduce the number of vehicle stops and shockwave impact on the traffic conditions . Hence, this study has further explored the following objective function of minimizing the speed variance along the target freeway for a VSL control: min0.25emtruektrueiuikuave2where, u ave is the average speed of the target freeway stretch, and is given as follows: uave=kiuik()Tctrue/normalΔTN…”
Section: Basic Proactive Control Modelmentioning
confidence: 89%
“…The VSL is initially designed to reduce the speed difference on some hazardous highway segments so as to decrease the rear‐end collisions and improve traffic safety . Recently, it has been recognized that VSL may also offer the potential to mitigate traffic congestion and improve traffic efficiency at work‐zones and freeway bottlenecks.…”
Section: Introductionmentioning
confidence: 99%
“…However, including only free-flow speeds does not allow the researcher to include traffic characteristics as explanatory variables when estimating operating speeds. Previous researchers have included traffic characteristics in the speed model specification, which provides insights to the range of speeds observed on a highway segment while still allowing evaluation of predicted free-flow speeds by setting traffic flow to a low value (27,28). This speed modeling practice also allows exploration of speed-highway geometry relationships at all points along the speed-flow curve.…”
Section: Free-flow Speedsmentioning
confidence: 99%